Using Paradox to Build Management and Organization Theories - Poole, Marshall Scott; Ven, Andrew H. Van de (Academy of Management Review, 1989)
Most contemporary theory construction methodologies attempt to build internally consistent theories of limited scope. Relatively little attention has been paid to the opportunities offered by tensions, oppositions, and contradictions among explanations of the same phenomenon. This essay attempts to spell out a set of theory-building strategies to help researchers take advantage of theoretical tensions. Such tensions can be regarded as paradoxes of social theory, and four different modes of working with paradoxes can be distinguished: (1) accept the paradox and use it constructively; (2) clarify levels of analysis; (3) temporally separate the two levels; and (4) introduce new terms to resolve the paradox. These four modes of paradox resolution are illustrated by application to the action:.-structure paradox in organizational theory.